Scientific literacy on the topic of light and optical instruments in the innovation of science teaching materials - Fahmi Fahmi; Nur Chalisah; Maya Istyadji; Yudha Irhasyuarna; Muhammad Kusasi (Jurnal Inovasi Pendidikan IPA, 2022)
This study aims to innovate science teaching materials based on scientific literacy on light and optical instruments. The study used the research and development (RD) method with the four-D (4D) model. The subjects in the study included three experts and 60 class VIII students with an age range of 13-15 years at the same level. This study collected quantitative data from product validation, questionnaire, and scientific literacy test. The questionnaire and test instrument have been proven valid and reliable based on expert judgment and empirical tests. The data were analyzed using descriptive and empirical statistic tests. The expert judgment proves that science teaching materials score 3.79 of 4 and scientific literacy aspects 3.71 of 4, which is valid. In addition, the teaching materials were also categorized as effective with an overall score (z = -4.731 and p-value = 0.000 0.05). In detail, the learning process increases student scientific literacy (p-value = 0.0000.05). Furthermore, science teaching materials based on scientific literacy could be optimized to improve students' scientific literacy skills sustainably.